2006
DOI: 10.1007/s11099-006-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid composition and photochemical activity of four sandy grassland species

Abstract: The photosynthetic pigments and photochemical efficiency of photosystem 2 (PS2) were studied in four constitutive species (Achillea millefolium L., Festuca pseudovina Hack. ex Wiesb., Potentilla arenaria Borkh., and Thymus degenianus Lyka) of a semiarid grassland in South-eastern Hungary. Every species displayed typical sun-adapted traits and substantial plasticity in the composition and functioning of the photosynthetic apparatus. The contents of chlorophylls (Chls) and carotenoids (Cars) on a dry matter basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…When high-temperature stress occurred, the amounts of total Cars increased significantly compared to Chl and other photosynthetic pigments. A similar finding was reported by Veres et al (2006) who showed that in high-temperature environment, the content of total Cars increased markedly in psammophytes during the summer compared with Chl. Havaux et al (1996) reported that the dark-adapted leaves employed a sophisticated, rapid biosynthetic mechanism to produce extra xanthophylls under heat stress.…”
Section: Effects Of Elevated Temperature On Psiisupporting
confidence: 89%
“…When high-temperature stress occurred, the amounts of total Cars increased significantly compared to Chl and other photosynthetic pigments. A similar finding was reported by Veres et al (2006) who showed that in high-temperature environment, the content of total Cars increased markedly in psammophytes during the summer compared with Chl. Havaux et al (1996) reported that the dark-adapted leaves employed a sophisticated, rapid biosynthetic mechanism to produce extra xanthophylls under heat stress.…”
Section: Effects Of Elevated Temperature On Psiisupporting
confidence: 89%
“…A high q P was beneficial to increase electron transport and quantum yield, which was confirmed by the higher F v '/F m ' and ETR of F. delavayi relative to F. cirrhosa. NPQ represented the energy dissipated as heat (Veres et al 2006), and redundant energy becomes a potential source of damage to the photosynthetic apparatus (Melis 1999). F. delavayi had a high NPQ, which could protect photosynthetic reaction centres from damage induced by irradiation.…”
Section: Correlations Between P N and Environmental Factorsmentioning
confidence: 99%
“…The resulting surplus of energy becomes a potential source of damage to the plant (Melis 1999), as it can lead to formation of destructive oxidative molecules, which can damage the photosynthetic apparatus in photoinhibition (Aro et al 1993), and the q NP can represent the energy dissipated as heat energy (Vasil'ev et al 1998, Veres et al 2006, which can not be utilized to transport photosynthetic electrons. The higher q NP in C. praecox showed that the energy absorbed in the physiological range of irradiances might be much higher than photochemical utilization.…”
Section: Chl Fluorescencementioning
confidence: 99%